Quality of kiwis minimally processed and treated with ascorbic acid, citric acid and calcium chloride - Carvalho, Ana Vânia; Lima, Luiz Carlos de Oliveira (Pesquisa Agropecuaria Brasileira, 2002)
Minimally processed fruits and vegetables might present the same convenience and quality of fresh products. In this work, the influence of minimal processing of fruits treated with 1% solutions of ascorbic acid, citric acid and calcium chloride on the quality of kiwi (Actinidia deliciosa cv. Hayward), during refrigerated storage were investigated. Mass loss was minimal over the storage period. Ascorbic acid furnished by the treatment was effectively absorbed by tissues, keeping the vitamin C levels 25% higher in those fruits, than in other treatments. Microbiological analysis detected the presence of the group molds and yeasts and psychrotrophic in citric acid treatment, at 8 and 10 days, respectively. Total and faecal coliforms and mesophyles were not found, indicating that processing was performed under good hygienic conditions. Minimally processed and calcium chloride treated kiwis presented a ten-day shelflife. For other treatments and for control, shelflife was six days.